Evaluation of primary repair of common bile duct in common bile duct stones - Mohamed A Abdel-Raheem; Abdelmonem A Mohamed; Emad A Ibrahim; Mohamed B Gaber (Wolters Kluwer Medknow Publications, 2016)
Background Despite advancements in gallbladder surgery with the introduction of endoscopic and laparoscopic techniques, many surgeons, especially in the developing world, still perform open cholecystectomy with common bile duct (CBD) exploration for choledocholithiasis. Aim of the study The purpose of the study was to report the outcomes of open CBD exploration without the use of T-tubes. Materials and methods A prospective study of open CBD exploration and primary closure was performed without T-tube drainage. Preoperative investigations, the surgical techniques, and perioperative outcomes were recorded. Results Fifty patients had CBD exploration. In 45 patients this was performed by means of a supraduodenal choledochotomy, and in five of these patients free passage into the duodenum could not be achieved using catheters, irrigation, and dilators. These were completed with a choledochoduodenostomy. Conclusion In a limited resource setting, there is still a role for open CBD exploration and primary closure without the necessity of T-tubes and stents as evidenced by a good perioperative patient outcome.